Analysis of combined heat and mass transfer of water-vapor in a cylinderical zeolite adsorber - Assefa, Abebayehu (Zede Journal of Ethiopian Engineers and Architects, 2023)
Jn this paper, the combined heat and mass transfer of water-vapor into a cylindrical zeolite adsorber has been numerically simulated The twodimensional heat and mass transfer equations are numerically solved using gPROMS program - a general Process Modeling System [J] program, inserting the proper initial and boundary conditions to the model. The centered finitedifference method (CFDM) approximation is employed in solving the two-dimensional partial differential equations. The validity of the developed model has been checked against an experimental study [2} conducted at the Institute of Technical Thermodynamic, Aachen - Germany, where this simulation study has been carried out. The complex experimental rig has been built to investigate the water vapor uptake of zeolite layers of defined cylindrical dimensions. The results of the experimental investigation and the numerical simulation show a very good fit with a maximum error of approximately 4%